Health and Illness in T’en-T’ai Buddhism and Nichiren Teaching. An Overview - Takahashi, Satoko (Acta Orientalia Vilnensia, 2001)
Buddhism presumes that all living beings suffer. Even the Buddha is said to have had a little illness and a little suffering (Daichido-ron: Kawada, 1975, p. 33). An ideal health in Buddhism is, therefore, not an absence of illness.The goal of Buddhism is to attain human happiness. The question is not if one has an illness or not but if a person is happy with or without being ill. Nichiren (MW. If. 5, p. 280) wrote to a woman (Myoshin-ama) in the face of her husband’s critical illness. “... illness does not necessarily result in death. Now, this illness of your husband’s may be due to the Buddha’s design, for the Vimalakirti and Nirvana sutras both speak of sick people attaining Buddhahood. From illness arises the mind that seeks the Way.” In chapter fifteen chapter of the Lotus Sutra, the four great bodhisattvas asked the Buddha: “Is the World-Honored One comfortable, with few illnesses, few worries?” The Buddha answered: “Just so, just so, good men! The Thus Come One (Buddha) is well and happy. with few i1Is and few worries.” (Watson, 1993, p. 214)“Health” in Buddhism is the life condition of the Bodhisattva. The Bodhisattva is basically healthy both physically and mentally. He wi1l become sick not because of his own weakness in his body or mind but because of the unhappiness of others. Bodhisattvas need training. They put themselves into circumstances where people are suffering, and physical, chemical, biological and psychological stresses are manifest (Kawada, 1983). Ikeda (1998) concludes: “Health means the life condition of the Bodhisattva. People are healthy when they dedicate themselves to others.” Rene Dubos (1959) said: “It is a lazy dream to imagine a life without anxiety and stress. Since human lives are dynamic processes, while the idea of utopia is static, it is useless to try to find a utopia on the earth.... Each human being fights not necessarily for the sake of himself, but for the emotional, intellectual, and ethical development of all human beings. To grow in the middle of danger itself is the law of life which is our destiny.” In other words, Buddhism puts emphasis on spiritual strength with a committed sense of mission or purpose of life through a compassionate action for others.